Special Education Teacher Preparation for Family–Professional Partnerships: Results From a National Survey of Teacher Educators. (November 2019) - Kyzar, Kathleen B.; Mueller, Tracy Gershwin; Francis, Grace L.; Haines, Shana J.
Family–professional partnerships (FPPs) are an important, federally mandated part of the American education system that benefit all students, but especially students with disabilities. Although special education teacher preparation programs offer a viable and sustainable way to enhance FPPs, little is known about the degree to which these programs address FPPs within their curricula. The purpose of this study was to examine the ways in which special education teacher preparation programs address FPPs. A total of 113 special education faculty members across 52 institutions responded to a national online survey addressing this topic. Results indicated (a) a disconnect in the value and implementation of FPP-related knowledge and skills at the program and individual faculty levels and (b) patterns of inconsistent FPP-related content coverage across undergraduate and graduate offerings as well as across FPP-specific and non-FPP-specific coursework. Implications for practice and future research are discussed.